Analisis Perubahan Kurikulum di Indonesia & Pengembangan Pendekatan Understanding By Design - Friska Amalia; Lutfi Asyari (Institut Pendidikan Indonesia, 2023)
Education is a very important factor in human life, because education can make it easier for people to develop their interests, talents and personality, as well as to understand various knowledge about everything related to the world. In managing the educational process there are components that have a strategic role, namely the curriculum. The curriculum is a learning program to achieve institutional goals in educational institutions, so that the curriculum has an important role in realizing quality learning. Indonesia has experienced many curriculum changes and curriculum changes are considered to determine the future of students in a nation. The implementation of the independent curriculum is a change and development of the previous curriculum. The new paradigm of learning has the principle that the learning process is differentiated so that each lesson is adapted to the needs and level of development. Independent curriculum development is expected to use the approach Understanding by Design (UbD) which is expected to improve the curriculum in Indonesia.